BPcontrol - Carrera, Adrián; Pifarré, Marc; Vilaplana, Jordi; Cuadrado, Josep; Solsona, Sara; Mateo, Jordi; Solsona, Francesc (Applied Clinical Informatics, 2016)
Background Hypertension or high blood pressure is on the rise. Not only does it affect the elderly but is also increasingly spreading to younger sectors of the population. Treating this condition involves exhaustive monitoring of patients. The current mobile health services can be improved to perform this task more effectively.Objective To develop a useful, user-friendly, robust and efficient app, to monitor hypertensive patients and adapted to the particular requirements of hypertension.Methods This work presents BPcontrol, an Android and iOS app that allows hypertensive patients to communicate with their health-care centers, thus facilitating monitoring and diagnosis. Usability, robustness and efficiency factors for BPcontrol were evaluated for different devices and operating systems (Android, iOS and system-aware). Furthermore, its features were compared with other similar apps in the literature.Results BPcontrol is robust and user-friendly. The respective start-up efficiency of the Android and iOS versions of BPcontrol were 2.4 and 8.8 times faster than a system-aware app. Similar values were obtained for the communication efficiency (7.25 and 11.75 times faster for the Android and iOS respectively). When comparing plotting performance, BPcontrol was on average 2.25 times faster in the Android case. Most of the apps in the literature have no communication with a server, thus making it impossible to compare their performance with BPcontrol.Conclusions Its optimal design and the good behavior of its facilities make BPcontrol a very promising mobile app for monitoring hypertensive patients.Citation: Carrera A, Pifarré M, Vilaplana J, Cuadrado J, Solsona S, Mateo J, Solsona F. BPcontrol: a mobile app to monitor hypertensive patients
Keywords: Hypertension; telemedicine and telehealth; remote monitoring